Da tertúlia ao portal : experiências de jornalistas de Cuiabá-MT (1968-1997) - Costa, Laís Dias Souza da (2019)
This research analyzes the life experiences and work of seven journalists who act or acted in the press of Cuiabá, and reunite oral history, history through press, discourse studies, as well as gender and feminist studies. The creation of the newspaper Diário de Cuiabá is the milestone of this thesis, which presents three generations of journalists, and the most important features of journalism put into practice since the period when there was the professionalization of the area, in the late 1960s until 1997 when they launched their website. Journalism is presented since the period of “meeting”, characterized by an empirical and self-taught practice, until the appearing of “new” journalism, which preconizes a group of standards and rules, as much technical as ethical, and altered, little by little, journalism practices, which was considered a mere occupation regarding a profession. The organization of the category of journalists, in the state of Mato Grosso, since the creation of a professional association, in 1969, then turned into a union in 1972, is also described in this thesis, as well as the memories of journalists from different places and some journalistic aspects that were practiced during the 1980s. The “feminization” of the profession and the discussion on gender issues in the newsroom are also present, besides the discussion on the category of “objectivity” and the implications of the journalism practiced in the 1990s, nationaland locally, with the computerization and repercussion of denunciations and dossiers.